(untitled) (Communications in Computational Physics, 2018)
Cortical spreading depression (CSD) involves depolarization of neurons and astrocytes due principally to a large increase in extracellular potassium. CSD is also accompanied by large increases in extracellular ATP and is blocked by glutamate N-methyl-D-aspartate (NMDA) receptor antagonists. In a previous study, we used a neuronal model to investigate the instigation of CSD and propagation of CSD wave by increasing extracellular potassium. In this paper, we extend that model by constructing a neuron-astrocyte network and incorporating the effects of ATP via the coupled biochemical pathways involving glutamate and NMDA currents. We show that both the electrical current stimuli and the local elevation in the extracellular ATP or glutamate concentration can lead to CSD in the coupled neuron-astrocyte model, while ATP or glutamate increase fails to induce CSD when the glutamate NMDA channels are blocked. These results can explain both the potassium theory postulated by Grafstein and glutamate theory by Van Harreveld. Our model showed extracellular potassium plays the key role in CSD instigation and propagation, and glutamate is a key compound mediating CSD by activating NMDA channels through neuron-astrocyte interactive.